2022
DOI: 10.3390/pharmaceutics14010190
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Glucosinolates from Cruciferous Vegetables (Brassicaceae) in Gastrointestinal Cancers: From Prevention to Therapeutics

Abstract: The gastrointestinal (GI) tract is composed of rapidly renewing cells, which increase the likelihood of cancer. Colorectal cancer is one of the most frequently diagnosed GI cancers and currently stands in second place regarding cancer-related mortality. Unfortunately, the treatment of GI is limited, and few developments have occurred in the field over the years. With this in mind, new therapeutic strategies involving biologically active phytocompounds are being evaluated as anti-cancer agents. Vegetables such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 123 publications
0
22
0
Order By: Relevance
“…Brassicaceous vegetables have been receiving scientific attention for many years because numerous studies reported that eating these vegetables would reduce the risk of some chronical diseases and kinds of cancer [ 46 , 47 ]. The main reason for that is that brassicaceous vegetables contain various phytonutrients such as the polyphenol, glucosinolates, carotenoid or terpenoid groups.…”
Section: Discussionmentioning
confidence: 99%
“…Brassicaceous vegetables have been receiving scientific attention for many years because numerous studies reported that eating these vegetables would reduce the risk of some chronical diseases and kinds of cancer [ 46 , 47 ]. The main reason for that is that brassicaceous vegetables contain various phytonutrients such as the polyphenol, glucosinolates, carotenoid or terpenoid groups.…”
Section: Discussionmentioning
confidence: 99%
“…The mean adduct level was corrected across experiments based on the recovery of the carcinogen-adducted DNA standards: one prepared in vitro by the reaction of B(a)P diolepoxide (BPDE, 3 H-labeled) with DNA according to a published method [20], while the other consisted of a DNA sample extracted i.p. from the hepatic tissue of four mice treated with 1.0 mg of [7, H]B(a)P for 24 h [21]. The level of B(a)P adducts in the livers of the B(a)P-treated experimental animals was also quantified as B(a)P-tetrols released from the hydrolysis of macromolecules and measured by GC-MS [21].…”
Section: Dna Adduct Analysismentioning
confidence: 99%
“…A randomized controlled trial examining the association between antioxidant vitamin supplementation and DNA damage has found a significant protective effect but only among women, and a cross-sectional investigation showed an inverse association of DNA damage with the plasma levels of certain micronutrients, such as retinol, α-tocopherol and γ-tocopherol [5]. Moreover, certain kinds of foods contain bioactive compounds with antioxidant and anti-inflammatory properties that can be used to develop prevention programs against chronic diseases, such as cardiovascular disease, neurodegenerative disease and gastrointestinal cancer [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported the anticarcinogenic activity of several metabolites found in cruciferous vegetables. For example, glucosinolates, a secondary metabolite mainly found in cruciferous plants, display activity in preventing the development and progression of gastrointestinal cancers as well as in treating these cancers ( 11 ). To date, the existence of more than 130 glucosinolates has been reported which can be classified into three major structural groups i.e., aliphatic, indole, and aromatic glucosinolates ( 12 ).…”
Section: Introductionmentioning
confidence: 99%